Trust, Perceived Quality, and Value for Money as Determinants of Customer Loyalty: Insights from the inDrive App - Putra, Wira Pramana; Supriyanto, Wawan; Noraga, Gilang Bhirawa; Tarjono (Junal Ilmu Manajemen, 2025)
One of the industries affected by the growth in the number of internet users and advances in digital technology in Indonesia is online transportation. However, the inDrive company showed the smallest performance, which only reached 4.03 million downloads, this merchant was very far behind its competitors, namely Gojek, Grab and Maxim. InDrive has implemented a unique concept, namely the bidding feature in order to achieve fairness and transparency and maximize services with the SHIELD security feature. Therefore, this study aims to identify the effect of value for money, perceived quality on trust, mediate trust in value for money and perceived quality on customer loyalty, and trust in customer loyalty. This research is a quantitative study, with data sources obtained from online questionnaires distributed to 130 respondents who have used the inDrive application in Indonesia who were analyzed using the Structural Equation Model on SmartPLS. The findings of this study are that perceived quality and value for money has a positive and significant effect on trust, trust mediates perceived quality and value for money on customer loyalty and trust has a positive and significant effect on customer loyalty. Trust is the most significant variable affecting customer loyalty, so inDrive Indonesia management must focus on maintaining consistency and increasing consumer trust